RESPON MASYARAKAT DAYAK TERHADAP ORGANISASI KRISTEN DI BORNEO PADA TAHUN 1928-1930 - Kurni, Raden Riski Maulana Al; Azmi, Muhammad; Marfuah, Siti (Amarthapura: Historical Studies Journal, 2022)
This During the period between 1928 and 1930, Christian religious organizations entered the Borneo region with the primary intention of spreading the teachings of Christianity to the Dayak community. The Dayak people, living in a unique and culturally rich social environment, serve as the primary focus of this research. This article aims to investigate and comprehend the responses exhibited by the Dayak community to the presence of Christian religious organizations, exploring the influences generated by such interactions, and analyzing the roles and responses of the Dayak people in the face of this new religious influx. The Dayak community, with its complex social structure and strong cultural beliefs, provides an intriguing context for understanding how Christian teachings permeated and interacted with the local culture. Christian organizations during this period were committed to disseminating their religious doctrines while concurrently providing education and support for community development. The responses of the Dayak community to these efforts varied significantly, encompassing partial acceptance, partial rejection, and the preservation of their existing beliefs and culture. The research findings offer insights into the complex dynamics of cultural changes occurring within the Dayak community during this period. Cultural conflicts, adaptive processes, and the struggles over religious values contribute to the cultural diversity that characterizes Borneo.